Multi-Scope Feature Extraction for Intracranial Aneurysm 3D Point Cloud Completion - Wuwei Ma; Xi Yang; Qiufeng Wang; Kaizhu Huang; Xiaowei Huang (Cells, 2022)
3D point clouds are gradually becoming more widely used in the medical field, however, they are rarely used for 3D representation of intracranial vessels and aneurysms due to the time-consuming data reconstruction. In this paper, we simulate the incomplete intracranial vessels (including aneurysms) in the actual collection from different angles, then propose Multi-Scope Feature Extraction Network (MSENet) for Intracranial Aneurysm 3D Point Cloud Completion. MSENet adopts a multi-scope feature extraction encoder to extract the global features from the incomplete point cloud. This encoder utilizes different scopes to fuse the neighborhood information for each point fully. Then a folding-based decoder is applied to obtain the complete 3D shape. To enable the decoder to intuitively match the original geometric structure, we engage the original points coordinates input to perform residual linking. Finally, we merge and sample the complete but coarse point cloud from the decoder to obtain the final refined complete 3D point cloud shape. We conduct extensive experiments on both 3D intracranial aneurysm datasets and general 3D vision PCN datasets. The results demonstrate the effectiveness of the proposed method on three evaluation metrics compared to baseline: our model increases the F-score to <semantics>0.379</semantics> (<semantics>+21.1%</semantics>)/<semantics>0.320</semantics> (<semantics>+7.7%</semantics>), reduces Chamfer Distance score to <semantics>0.998</semantics> (<semantics>−33.8%</semantics>)/<semantics>0.974</semantics> (<semantics>−6.4%</semantics>), and reduces the Earth Mover’s Distance to <semantics>2.750</semantics> (<semantics>17.8%</semantics>)/<semantics>2.858</semantics> (<semantics>−0.8%</semantics>).